2021
DOI: 10.2147/idr.s331468
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and Phenotypic Characteristics for Vibrio vulnificus Infections

Abstract: Background Vibrio vulnificus (VV) is a causative agent of foodborne diseases with high mortality. The aim of this study was to investigate the genomic and phenotypic profiles of VV. Methods Six VV isolates were collected and conducted whole-genome sequencing. Biofilm formation and anti-complement killing test were performed to evaluate the pathogenicity. Subsequently, 157 publicly available genomes of VV isolates were selected to determine the evolutionar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The genome of V. vulnificus has 11 putative RND efflux pump-encoding genes, three of which (homologues of V. cholerae VexAB, VexCD, and AcrAB of E. coli) have been characterized by gene deletion studies [50]. A study identified the norM gene in whole-genome sequences of clinical V. vulnificus isolates [65]. While a mutant V. vulnificus lacking the vexAB homolog was more susceptible to erythromycin, acriflavine, ethidium bromide, and bile acid, deletion of acrAB homolog resulted in increased sensitivity of acriflavine alone, and vexCD deletion did not have any effect on the susceptibility to any of the antibiotics, dyes or bile acid [66].…”
Section: Efflux Pumps Of Rnd Family In Vibrio Speciesmentioning
confidence: 99%
“…The genome of V. vulnificus has 11 putative RND efflux pump-encoding genes, three of which (homologues of V. cholerae VexAB, VexCD, and AcrAB of E. coli) have been characterized by gene deletion studies [50]. A study identified the norM gene in whole-genome sequences of clinical V. vulnificus isolates [65]. While a mutant V. vulnificus lacking the vexAB homolog was more susceptible to erythromycin, acriflavine, ethidium bromide, and bile acid, deletion of acrAB homolog resulted in increased sensitivity of acriflavine alone, and vexCD deletion did not have any effect on the susceptibility to any of the antibiotics, dyes or bile acid [66].…”
Section: Efflux Pumps Of Rnd Family In Vibrio Speciesmentioning
confidence: 99%
“…Furthermore, dfrA31 is an antibiotic resistance dihydrofolate reductase from an integron found in V. cholerae with target replacement as its resistance mechanism (Roberts et al, 2012;Zankari et al, 2012). Intriguingly, this gene can also be found in V. vulnificus isolates 25506, infecting humans in China (Zhang et al, 2021). Another interesting ARG that may affect SXT resistance was dfrA6 in CUVETCC1, which is also found in V. vulnificus (Vv1462) Hong Kong isolates from China.…”
Section: Sulfonamides and Diaminopyrimidine Resistomementioning
confidence: 99%